Reading for Action: Engaging Youth in Social Justice through Young Adult Literature - Boyd, Ashley S.; Darragh, Janine J. (Rowman & Littlefield Publishers, 2019)
This book illustrates how teachers can draw upon young adult literature to facilitate students’ social action. Each chapter centers on one novel that represents a contemporary topic including police brutality, women’s rights, ecojustice, and bullying. In each, authors provide pre-, during-, and after reading strategies for teaching that connect the social issues in the texts to students’ lives and to the world around them. They then offer a multitude of avenues for student action, emphasizing the need to move readers from understanding and awareness to asserting their own agency and capacities to effect change in their local, national, and global communities. In addition to methods for scaffolding students’ analysis of texts and topics, authors also offer a plethora of additional resources such as documentaries, canonical companions for study, connected music, and supplementary lesson plans.